Eventyret Antarktis - Børde, Haakon; Johansen, Karl Hans (Gyldendal, 1978)
Keywords: Antarktis; Norge; Norsk Polarinstitutt; Sydpolsekspedisjonen; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Med Amundsen til Sudpolen. Dagbokblad - Bjaaland, Olav (Syn og segn, 1975)
Keywords: Antarktis; Roald Amundsen; Sydpolen; dagbok; ekspedisjoner; oppdagelsesreiser; polarområdene

Norsk polarpolitikk : hovedtrekk og utviklingslinjer 1905-1974 - Skagestad, Odd Gunnar (Dreyers Forlag, 1975)
Keywords: Antarktis; Norge; historie; polarforskning; polarområdene; polarpolitikk; statsforvaltning

The New Development in the Polar Regions - Sollie, Finn (Cooperation and Conflict, 1974)
Due to factors connected with modern technological developments and with the increasing global demand for new sources of raw materials, there is today a growing interest in the possibilities for economic exploitation of the polar regions. This makes for a new development in these regions; a development comprising and affecting such fields as science and technology as well as economy, transportation, military strategy and ecology. The present paper discusses this new development and its implications in an international perspective. Special attention is paid to the significance - in the physical/ geographical sense and otherwise - of the polar regions in the global context. A special section deals, on a general level, with 'the problem of the new territories', and the polar regions are discussed as new territories. Pointing out the risks and dangers inherent in the present and emerging developments, the author emphasizes the need for action, especially international cooperation, to meet and solve such problems. Cooperation may be facilitated through regular consultations between the states concerned, as is the case under the Antarctic Treaty. For the Arctic in particular, the author suggests a distinction between three basic zones (viz. the 'Central' the 'Intermediate' and the 'National' Arctic) as a possible point of departure for future discussion of measures of international cooperation.
Keywords: Antarktis; internasjonal politikk; polarområdene

Kappløpet mot Sydpolen - Jonason, Jan (Tiden, 1971)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene